Medpropozicijskost z vidika družljivosti glagolov oz. povedkov - Žele, Andreja (Slavia Centralis, 2014)
As the co-reference of propositions within a complex sentence or text, inter- proposition enables the inter-dependent co-occurrence of predicates or, rath - er, predicative optionality, as well as relative meanings, which are marked by connectors. This article treats inter-proposition from the standpoint of possible predicative co-occurrences within a sentence.
Keywords: glagolske kategorije; medpropozicijskost; povedkova kookurenčnost; povedkova sopojavnost; Slovene; slovenščina